(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article examines the conceptual foundations of spiritual and moral education as a primary factor in constructing the Third Renaissance in New Uzbekistan. The study analyzes the historical continuity between the previous Eastern Renaissances and current educational reforms. By employing qualitative analysis of state decrees and pedagogical strategies, the paper identifies the integration of national values with modern professional competencies. The results suggest that the "Third Renaissance" is not merely an economic or technological goal but a cultural transformation rooted in high spirituality. The findings conclude that a balanced approach between "secular knowledge" and "moral upbringing" is essential for developing competitive personnel.